Standing frontonasal flap and maxillary sinus trephination in a horse with sinusitis - Khairuddin, Nurul Hayah; Mohamad, Mimi Armiladiana (Universiti Putra Malaysia Press, 2016)
This report describes use of a standing frontonasal bone flap (SFF) technique to treat a case of primary sinusitis affecting the right frontal and maxillary sinuses in a horse. The diagnosis was made based on a history of prolonged unilateral nasal discharge, endoscopy and radiographic findings. A frontonasal bone flap was created and maxillary sinus trephination was performed while the horse was standing and sedated. Standing sedation throughout the whole procedure was achieved through constant rate infusion (CRI) technique with detomidine hydrochloride. The outcome of this case confirmed that standing frontonasal flap surgery provides an effective method to specifically treat primary sinusitis in a horse and eliminates the risk of general anaesthesia in order to perform such invasive surgery.